Korelasi Penggunaan Metode ERACS terhadap Kualitas Hidup Ibu dan Anak di Rumah Sakit Bina Sehat - Efendi, Erfan; Sisdayani, Alfina Galuh Hannie; Safitri, Athiyah Naura (Faculty of Medicine, Universitas Padjadjaran, 2025)
Background: The Caesarean section (CS) rate has increased every year. However, this increase is not entirely due to medical indication. This phenomenon may put bot mothers and newborns at risk of short- and long-term complications associated with CS. Enhanced recovery after caesarean surgery (ERACS) is CS approach that incorporates preoperative, intraoperative, and postoperative. This study compared maternal and neonatal outcomes between ERACS and conventional caesarean delivery.Methods: A retrospective cohort study was conducted using medical records of caesarean deliveries at Bina Sehat Hospital, Jember (Sep tember2022–Aug 2023). Fifty ERACS and fifty conventional cases were included. Outcomes were early ambulation (≤12 h), length of stay (≤2 days), and good APGAR score (7–10) at 1 and 5 minutes. Data were analyzed using chi-square test.Results: Early ambulation (≤12 h) occurred in 38/50 ERACS VS 18/50 conventional cases. Leng of stay ≤2 days occurred in 40/50 ERACS vs 15/50 conventional cases. Good APGAR score in first minute 38/50 ERACS vs 37/50 conventional cases and in fifth minute 48/50 ERACS vs 49/50 conventional cases. The relationship between postoperative ambulation and length of stay is significant.Discussion: Preoperative, intraoperative, and postoperative modifications can accelerate patient mobilization after caesarean section. In addition, early ambulation improves various body functions related to metabolism. Theses factor has direct impact on postoperative ambulation and shorter length of stay.Conclusion: ERACS was associated with higher rate of early postoperative mobilization and shorter hospital length of stay compared with conventional caesarean delivery.